2011
DOI: 10.1021/tx100426s
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioavailability of Polyaromatic Hydrocarbons in the Form of Mucin Complexes

Abstract: Increasing exposure of biological systems to large amounts of polycyclic aromatic hydrocarbons is of great public concern. Organisms have an array of biological defense mechanisms, and it is believed that mucosal gel (which covers the respiratory system, the gastrointestinal tract, etc.) provides an effective chemical shield against a range of toxic materials. However, in this work, we demonstrate, for the first time, that, upon complexation of polyaromatic hydrocarbons with mucins, enhanced bioavailability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Here, 29 we demonstrate that mucin glycoproteins, the gel-forming constituents of native mucus, are suitable for 30 assembly into robust hydrogels capable of facilitating the sustained release of hydrophobic and hydrophi- 31 lic drugs. Covalently-crosslinked mucin hydrogels were generated via exposure of methacrylated mucin 32 to ultraviolet light in the presence of a free radical photoinitiator.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Here, 29 we demonstrate that mucin glycoproteins, the gel-forming constituents of native mucus, are suitable for 30 assembly into robust hydrogels capable of facilitating the sustained release of hydrophobic and hydrophi- 31 lic drugs. Covalently-crosslinked mucin hydrogels were generated via exposure of methacrylated mucin 32 to ultraviolet light in the presence of a free radical photoinitiator.…”
mentioning
confidence: 89%
“…We characterize mucin hydro-123 gels rheologically and investigate the loading and release from 124 mucin hydrogels of polymyxin B, a positively-charged hydrophilic 125 antibacterial drug, and paclitaxel, a hydrophobic anti-cancer drug. 126 We demonstrate the sustained release from mucin hydrogels of [30] as well as binds 344 and solubilizes water-insoluble aromatic hydrocarbons, enhancing 345 their bioavailability [31]. 346 We methacrylated BSM following methacrylation protocols 347 previously applied to other biopolymers, including gelatin 348 [32,33], dextran [34], chitosan [35], chondroitin sulfate [36], and 349 hyaluronic acid [37], but never before to mucin.…”
mentioning
confidence: 95%
“…Among their chemical properties, mucins may act as moisture holders, adhesins, and solubilizers, as well as reducing agents and surfactants (18). Some of us have shown that BSM, a representative natural mucin, is capable of binding and solubilizing various types of polycyclic aromatic hydrocarbons in aqueous solutions, leading to increased antimicrobial activity (19). Further, a simple method was developed to generate Ag NPs inside a BSM matrix (20).…”
mentioning
confidence: 99%
“…23 We have shown that the guest concentrations of dyes or MWNT could be as high as 17 % 23. 24 Fluorescent BSM solutions and electro‐optical devices were prepared with the use of several types of hydrophobic emitting dye molecules as fillers.…”
mentioning
confidence: 99%